2013
DOI: 10.1523/jneurosci.1190-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

TheXenopusAmygdala Mediates Socially Appropriate Vocal Communication Signals

Abstract: Social interaction requires that relevant sensory information is collected, classified, and distributed to the motor areas that initiate an appropriate behavioral response. Vocal exchanges, in particular, depend on linking auditory processing to an appropriate motor expression. Because of its role in integrating sensory information for the purpose of action selection, the amygdala has been implicated in social behavior in many mammalian species. Here, we show that two nuclei of the extended amygdala play essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 57 publications
0
56
2
Order By: Relevance
“…DTAM also receives input from the central amygdala located in the ventral forebrain (Brahic and Kelley, 2003;Hall et al, 2013). Because previous work has also shown that removal of the midbrain and forebrain does not disrupt fictive calling in X. laevis (Yu and Yamaguchi, 2010), we predicted that species-specific LFP wave patterns are generated autonomously within the hindbrain compartment that includes DTAM.…”
Section: Species Share Similar Fictive Trill Ratesmentioning
confidence: 96%
“…DTAM also receives input from the central amygdala located in the ventral forebrain (Brahic and Kelley, 2003;Hall et al, 2013). Because previous work has also shown that removal of the midbrain and forebrain does not disrupt fictive calling in X. laevis (Yu and Yamaguchi, 2010), we predicted that species-specific LFP wave patterns are generated autonomously within the hindbrain compartment that includes DTAM.…”
Section: Species Share Similar Fictive Trill Ratesmentioning
confidence: 96%
“…As reviewed below, the essential developmental evidence across vertebrate lineages to support comparisons of a hindbrain CPG for patterning the activity of sonic muscles (larynx, syrinx, swim bladder) first became available only during the past few years . This led to the renaming of the sonic motor nucleus that innervates swim bladder muscles as the vocal motor nucleus, or VMN , a nomenclature that is followed here and has recently been adopted by studies of the amphibian laryngeal system (Hall et al 2013). …”
Section: Vocal-sonic Neuroanatomymentioning
confidence: 99%
“…Fictive calling – a pattern of nerve compound action potentials (CAPs) that matches temporal features recorded during actual calling [32; Fig. 2B] – can be reliably evoked in an isolated brain by raising endogenous serotonin using reuptake inhibitors, by serotonin application or by stimulating the amygdala [3335]. Vocal pattern generating circuitry is contained within the hindbrain and includes a more rostral, rhythmically active group of neurons located in the dorsal medulla at the level of cranial nerve V (DTAM, used as a proper noun) as well as interneurons and laryngeal motor neurons in the caudal hindbrain.…”
Section: Singing Without Breathing: Frogs and Fishmentioning
confidence: 99%
“…Taken together, these results indicate that hormone-sensitive vocal initiation must arise upstream of the hindbrain VPG. A strong candidate for initiation is a forebrain nucleus, the amygdala, that receives auditory input and innervates elements of the VPG [35] as described below.…”
Section: Development Of Vocal Pattern Generators; Modulators and Hormmentioning
confidence: 99%
See 1 more Smart Citation